A multidisciplinary approach in pre-pubertal child sexual assault cases – forensic evaluation and suggestions. (September 2022) - Kaur, Suminder; Kaur, Simarpreet; Rawat, Banita; Sharma, Rakesh
Highlights: Multidisciplinary and systemic evaluation of important factors including DNA analysis in order to pinpoint the cause. Significance of evidence selection and collection in pre-pubertal child sexual assaults. Aim to improve primary preventive strategies and identify potential setbacks obstructing the road to justice. Interplay between societal influences, family support, evidence collection, legal delays and medical hindrances affecting CSA analysis. To suggest stringent measures in order to prevent pre-pubertal sexual assault. Abstract: Background: Child sexual assault is highly prevalent in India yet a handful cases are reported under POCSO (Protection against child sexual offenses) Act, 2012. Even though the victims' testimony alone is enough to arrest accused as regulated by the Supreme Court but forensic evidence is still critical for sentencing rapists. A systematic evaluation of such cases will estimate impact of Child sexual assault (CSA) and pinpoint important aspects required for progression of prevention strategies and provision of support. Method and objective: Present study reviewed cases pertaining pre-pubertal victims (up to 10 years age). Study included simple descriptive analysis of data highlighting significance of different variables in sexual assault cases involving child victims- perpetration, interventions, medical examination and forensic DNA analysis with the aim to improve primary preventive strategies and identify potential setbacks obstructing road to justice. Result: The strengths and weaknesses of pre-pubertal sexual assault assessment were identified. This study analyzed socio-economic backgrounds, age of alleged accused and whether known to the victim. Frequently reported type of abuse was assessed and total reviewed cases that yielded DNA profile from exhibits of victims and alleged accused were determined. Conclusion: As emerged in present study, pre-pubertal CSA is a complicated phenomenon grounded in interplay between societal influences, family support, evidence collection, legal delays, and medical hindrances that greatly affect DNA analysis. Prevalence of CSA is evidently alarming and demands stringent measures to be taken to prevent and control it. Joint and multidisciplinary assessment is important for forensic reporting rather than solo assessment.